1965
DOI: 10.1002/jez.1401580303
|View full text |Cite
|
Sign up to set email alerts
|

Isozymes of isocitrate dehydrogenase: Subunit structure and intracellular location

Abstract: Isocitrate dehydrogenase (IDH) exists in mammalian tissues as three enzymes, one specific for NAD and two specific for NADP. The two NADP isozymes differ in electrophoretic mobility, immunological characteristics, and tissue and subcellular location. One is found mainly in the mitochondrial fraction and one in the supernatant fraction of tissue homogenates. Two allelic forms of the supernatant NADP isocitrate dehydrogenase have been described in inbred strains of mice. In a heterozygote containing both alleles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(42 citation statements)
references
References 66 publications
0
42
0
Order By: Relevance
“…Furthermore, expression of the cytosolic isoform of ICD (ICD1) is minimal in the heart, 38 and is several orders of magnitude lower relative to ICD1 expression in other tissues, including corneal epithelium, liver, kidney, and spleen. 39 Cytosolic ICD1 is therefore also unlikely to contribute significantly to the maintenance of cytosolic thiols. Furthermore, we found that in cardiomyocytes inhibition of G6PD caused a near complete depletion of total thiols and reduced glutathione.…”
Section: G6pd and Cardiomyocyte Redox Statementioning
confidence: 99%
“…Furthermore, expression of the cytosolic isoform of ICD (ICD1) is minimal in the heart, 38 and is several orders of magnitude lower relative to ICD1 expression in other tissues, including corneal epithelium, liver, kidney, and spleen. 39 Cytosolic ICD1 is therefore also unlikely to contribute significantly to the maintenance of cytosolic thiols. Furthermore, we found that in cardiomyocytes inhibition of G6PD caused a near complete depletion of total thiols and reduced glutathione.…”
Section: G6pd and Cardiomyocyte Redox Statementioning
confidence: 99%
“…Two alleles, Id-la and Id-l", were reported in inbred strains of mice (Henderson 1965;Roderick et al 1971;Staats 1976), and were also observed in the Western Hemisphere wild house mice, though the frequencies of the two alleles were variable among the populations investigated (Ruddle et al 1969;Hunt and Selander 1973;Berry and Peters 1977;Britton and Thaler 1978). One female carrying an Id-P allele has been found in the Hawaiian Islands (Wheelar and Selander 1972).…”
Section: Introductionmentioning
confidence: 98%
“…Haemoglobin was examined on the same gels used for the G6PD tests. The other enzyme systems were studied, using the procedures outlined by the original authors: phosphoglycerate kinase (Chen, Malcolm, Yoshida and Giblett, 1971), phosphohexose isomerase (Detter, Ways, Giblett, Baughan, Hopkinson, Povey and Harris, 1968), NADH diaphorase (Hopkinson, Gomey, Gook, Robson and Harris, 1970), isocitrate dehydrogenase (Henderson, 1965) and glutamic oxaloacetic transaminase (Davidson, Gortner, Rattazzi, Ruddle and Lubs, 1970).…”
Section: Red Cell Enzyme Groupsmentioning
confidence: 99%